Chemical composition of underground waters of Kharkiv region as a health risk factor of the population - Прибилова, В. М.; Качан, А. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The article discusses the results of public health risk assessment caused by the groundwater use without preliminary water treatment for residents of Kharkiv region. Within Kharkiv region the main aquifer used for centralized water supply is Palaeogene (usually Buchatskiy-Kanev, less Mezhygirska-Obukhiv), aquifer-loamy chalk strata of the Upper Cretaceous and Cenomanian-Inferior Cretaceous aquifer.Water quality has a direct impact on the incidence of local residents. Most of the rural population routinely uses water from their own wells or boreholes. In most of them water is low quality. Increased concentrations of Tl, Hg, Cd, Pb, As, Al, Ba, Sr, Fe, Mn have been found in untreated natural water sources in different parts of the region. As a rule, levels of most of the trace elements listed above are not reduced before drinking water reaches a consumer. The analysis of macro- and microcomponent composition of drinking underground waters of Kharkiv region has been carried out. Based on the chemical composition of groundwater in the main aquifers used for water supply purposes averaged over a large number of samples over a long period of observation, the main substances for assessing the health risk of the population were identified. Subject to applicable laws of chemical elements distribution in groundwater were received average concentrations of substances in each aquifer complex. All analyzes were carried out using modern water standard techniques quite widely used today to assess the quality of drinking water. The average daily doses of elements in the human body with consumed groundwater and the indices of non-carcinogenic effects for human health are calculated. Priority substances contained in groundwater and having a health hazard index of more than 0.05 are related to thallium, mercury, cadmium, lead, arsenic, barium, strontium, iron, and manganese. By the value of the total hazard ratio, a comparative analysis of the water quality of various aquifers has been carried out and a conclusion has been reached on the acceptability of the level of risk to human health.